The performance of gross pollutant trap for water quality preservation: a real practical application at the Klang Valley, Malaysia. Issue 52 (7th November 2016) - Sidek, L.; Basri, H.; Lee, L.K.; Foo, K.Y.
Abstract: The performance of a gross pollutant trap (GPT) was investigated at 51 catchments of the most polluted river in Malaysia, Klang River and its major attributes, Gisir River, Kemensah River, and Sering River for the entrapment of gross pollutants over the operation period of 10 months. The specific characteristics of gross pollutants generated from the different catchments were measured, and sorted into litter classification. The wet loads collected at the catchments ranged between 14 and 111 kg/ha, with majority of them was contributed by a significant amount of sediment and plastic. The water quality at the inflow and outflow channels was examined. GPT responded effectively for chemical oxygen demand, biological oxygen demand, ammonical nitrogen, and total suspended solids removal, reaching the maximum removal of 88, 94, 94, and 97%, respectively. The water quality index of the influent river water falls in Class V, derived as "very polluted, " while the downstream river water lies in the intermediate between Class IV and III, defined as "polluted" and "average, " respectively. These findings strongly supported the real practical applications of GPTs for the effective management and preservation of urban river systems.